2010
DOI: 10.1542/peds.2009-1862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gluten-free Camp on Quality of Life of Children and Adolescents with Celiac Disease

Abstract: OBJECTIVE-A gluten-free camp allows children with celiac disease (CD) to enjoy a camp experience without concern and preoccupation with foods they eat or the stigma of their underlying disease. The objective of this study was to evaluate the impact of gluten-free camp on quality-of-life indicators for children and adolescents with CD.METHODS-Children aged 7 to 17 years with CD were administered a 14-question survey at the beginning and the end of a 7-day gluten-free camp. Surveys used a Likert scale to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 16 publications
5
38
0
3
Order By: Relevance
“…Two of the seven clusters relate directly to positive interpersonal fulfilment (Nurturing Relationships, and Non-judgmental Environment and Attitude). These themes are consistent with literature with the positive social interaction and communication (e.g., Bongiovanni et al, 2010, Cushner-Weinsteine et al, 2007Kiveal, 2013;McAvoy et al, 2006), acceptance (e.g., Meltzer & Rourke, 2005), general satisfaction, fulfilment and wellbeing for campers with disabilities (Moons et al, 2006;Nettina et al, 2003, Wu et al, 2011. In addition to the social aspects, campers also report a sense of personal growth and empowerment, as in the "Independence and Recognition" and "Personal Growth" clusters.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two of the seven clusters relate directly to positive interpersonal fulfilment (Nurturing Relationships, and Non-judgmental Environment and Attitude). These themes are consistent with literature with the positive social interaction and communication (e.g., Bongiovanni et al, 2010, Cushner-Weinsteine et al, 2007Kiveal, 2013;McAvoy et al, 2006), acceptance (e.g., Meltzer & Rourke, 2005), general satisfaction, fulfilment and wellbeing for campers with disabilities (Moons et al, 2006;Nettina et al, 2003, Wu et al, 2011. In addition to the social aspects, campers also report a sense of personal growth and empowerment, as in the "Independence and Recognition" and "Personal Growth" clusters.…”
Section: Discussionsupporting
confidence: 90%
“…In their systematic review, Moola et al (2013) identified 21 studies of specialised therapeutic camps for children with chronic illnesses. The authors reported that in general, TR experiences tended to have some positive effects on the children with disabilities, including reduced aggression (Barr et al, 2010), improved wellbeing, self-perception, and emotional outlook (Bongiovanni, Clark, Garnett, Wojcicki, & Heyman, 2010), improved social and communication skills (Cushner-Weinsteine et al, 2007), increased self-esteem (Devine & Dawson, 2010;Torok, Kokonyei, Karolyi, Ittzes, & Tomcsanyi, 2006), improved self-management skills (Hunter, Rosnov, Koontz, & Roberts, 2006), higher peer acceptance (Meltzer & Rourke, 2005), better general physical and mental health functioning (Moons et al, 2006), better coping skills (Nicholas, Williams, & MacLusky, 2009), higher self-competence (Pulgaron, Salamon, Patterson, & Barakat, 2010), better quality of life (Shepanski et al, 2005), and general life satisfaction (Wu, Prout, Roberts, Parikshak, & Amylon, 2011). A range of other studies on specialised camps have also identified positive impacts for children with disabilities, including greater self-competence (Dawson & Liddicoat, 2009;Hill & Sibthorp, 2006), independence (Dawson & Liddicoat, 2009), social competence and sense of belonging (Dawson & Liddicoat, 2009;Lopata et al, 2010), positive parent-child communication skills (Walker, Barry, & Bader, 2010), care giving appreciation (Dawson & Liddicoat, 2009), ADHD symptom reduction (Hantson et al, 2012), diminished autism symptoms (Lopata et al 2010), reduction in anxiety (Briery & Rabian, 1999), and general physical and emotional empowerment, well-being, and satisfaction (Nettina, Donnelly, & Florio, 2003).…”
Section: Concept Mapping Analysis Of Social Skills Camp Experience Fomentioning
confidence: 99%
“…This phenomenon observed in most CD studies (6,9,22,26,35,36) could be because of the higher prevalence of the disease in females (3,7,8,18,(37)(38)(39)(40)(41)(42)(43), and also to their greater concern about the disease (7). We effectively observed that more mothers than fathers completed the questionnaire, as also reported by other authors (6,9,17).…”
Section: Discussionmentioning
confidence: 99%
“…Its origin is related with the presence of genes human leukocyte antigen (HLA)-DQ2 or HLA-DQ8, and both genotypes cause the predisposition for the disease [26], but 95% of CD patients exhibit the DQ2 serotype class [25]. In predisposed individuals, it can manifest in any stage of life, since that the contact with the protein fraction of wheat, barley, or rye was established [27].…”
Section: Celiac Disease (Cd)mentioning
confidence: 99%